1994
DOI: 10.1165/ajrcmb.10.4.8136156
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein A labeling kinetics in newborn and adult rabbits.

Abstract: Surfactant protein A (SP-A), the major hydrophilic protein specifically associated with surfactant, has multiple metabolic and host defense functions as well as primary surfactant biophysical functions in association with the other surfactant proteins and lipids. To characterize its kinetics of secretion and clearance from the airspace, we measured specific activity-time curves for alveolar and lamellar body associated SP-A following the intravascular and/or intratracheal administration of the radiolabeled pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
1
12
1
Order By: Relevance
“…This latter study postulated the rapid recycling (resecretion) of endocytosed SP-A through an early endosome. On the other hand, studies of the intact lung following endotracheal instillation of labeled SP-A have demonstrated its uptake from the alveolar space and subsequent appearance in lamellar bodies (15,18,19), as confirmed in the present study. One possibility for these different results is that the isolated type II cells had lost the mechanism for normal SP-A trafficking to lamellar bodies, consistent with their differentiation in culture and loss of other phenotypic characteristics.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This latter study postulated the rapid recycling (resecretion) of endocytosed SP-A through an early endosome. On the other hand, studies of the intact lung following endotracheal instillation of labeled SP-A have demonstrated its uptake from the alveolar space and subsequent appearance in lamellar bodies (15,18,19), as confirmed in the present study. One possibility for these different results is that the isolated type II cells had lost the mechanism for normal SP-A trafficking to lamellar bodies, consistent with their differentiation in culture and loss of other phenotypic characteristics.…”
Section: Discussionsupporting
confidence: 88%
“…However, there is less agreement concerning the intracellular trafficking of SP-A. Like SP-B and SP-C, SP-A is synthesized by type II cells and is secreted into the alveolar space, where it associates with the lung surfactant phospholipids (19,22,37). Extracellular SP-A appears to play crucial roles in the formation of tubular myelin, in the regulation of lamellar body exocytosis, and in the uptake of phospholipids by endocytosis and their subsequent remodeling (20,23,30,40).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…After opening the thorax, a short, blunt needle (ranging 14±22 gauge, depending on age) was inserted into the trachea. Five aliquots of saline at 48C were used to visibly fill the lungs as reported previously [10,15,16]. Each aliquot was flushed into and out of the airways three times.…”
Section: Isolation Of Large Aggregate Formsmentioning
confidence: 99%